Urucungo, Batuque and Amazonia: a comparison between the poetry of Bruno de Menezes and Raul Bopp - Freitas dos Santos, Joice (2024)
Bruno Menezes (1893 – 1963) and Raul Bopp (1898 – 1984) wrote and published modernist poetry on the same epoch, with thematic as the brazilian nature and black influence on historical and cultural country construction. Thus, the present article dedicate itself to do a collation between the poetries on the books Urucungo (1932): Urucungo, Mãe-Preta, Diamba, Negro and Caratateua; and Batuque (1931): Pai João, Mãe Preta, Liamba, Gente da Estiva and Igreja de Arrabalde. The objective was reflect about the similarities, as well as detach the differences and singularities of literary works. Proved that the texts has in common the fact of trace blackness characters on each poem, as well as the Africa chronological trajectory before the capture for enslavement, during the transportation by ships, life as slavers in Brazil and the descendant they received as heritage cultural manifestations filled with syncretism. Also, has in common the sonority and musicality well marked, use of themed groups’ dialect proper words. Indications that the two authors accomplished profound research about the chosen thematic universe.